2009
DOI: 10.1590/s0100-879x2009005000011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, ageing and night work

Abstract: Studies have shown that the frequency or worsening of sleep disorders tends to increase with age and that the ability to perform circadian adjustments tends to decrease in individuals who work the night shift. This condition can cause consequences such as excessive sleepiness, which are often a factor in accidents that occur at work. The present study investigated the effects of age on the daytime and nighttime sleep patterns using polysomnography (PSG) of long-haul bus drivers working fixed night or day shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
2
16
0
3
Order By: Relevance
“…Polysomnographic recordings were performed according to Pires et al [22]. Electrode placement was carried out according to the 10-20 system.…”
Section: Methodsmentioning
confidence: 99%
“…Polysomnographic recordings were performed according to Pires et al [22]. Electrode placement was carried out according to the 10-20 system.…”
Section: Methodsmentioning
confidence: 99%
“…(2) The presence of associated diseases, such as rhinitis (symptoms are present in 90% of cases), gastroesophageal Sleep 5 [16][17][18][19][20] Physiology, exercise, and rehabilitation 12 [21][22][23][24][25][26][27][28][29][30][31][32] COPD 8 [33][34][35][36][37][38][39][40] Pathology 3 [41][42][43] CT 2 [44][45] Occupational medicine 1 46 Pulmonary thromboembolism 2 [47][48] Pulmonary hypertension 3 [49][50][51] Lung cancer 3 [52][53][54] Smoking 2 [55][56] Evaluation of articles on pulmonology published in Brazilian In their study involving patients with severe OSAS, Neves et al found that the use of sildenafil worsens OSAS, as well as causing deleterious cardiovascular effects because of the increased parasympathetic tone and affecting the HR variability. (19) Pires et al, in a study of drivers engaged in night shift work, contradicted the notion that the sleep pattern of older individuals is more negatively affected than that of younger individuals.…”
Section: Asthmamentioning
confidence: 99%
“…(19) Pires et al, in a study of drivers engaged in night shift work, contradicted the notion that the sleep pattern of older individuals is more negatively affected than that of younger individuals. (20) Physiology, exercise, and rehabilitation…”
Section: Asthmamentioning
confidence: 99%
“…Ao estudar a relação de trabalho por turnos e noturno com as patologias do sono, estudiosos publicaram a influência destes na sociedade moderna, alterando os meios de produção e da organização do trabalho nas indústrias e mudando de forma drástica o estilo de vida, a saúde e o bemestar dos colaboradores 3 . Também mencionaram que turno contínuo e prolongado principalmente a noite predispõe os trabalhadores a doenças cardiovasculares, gastrointestinais e estresse psicossocial.…”
unclassified
“…Trabalhadores são rotineiramente submetidos à privação parcial crônica do sono devido ao desacordo recorrente entre o tempo de serviço e os horários fisiológicos de dormir. Sono mais curto e mais fragmentado implica em sonolência excessiva, fadiga mental, irritabilidade e redução do desempenho, que muitas vezes são fatores de risco para acidentes laborais 3 .…”
unclassified